The Influence of Enjoyment of Work and Job Crafting on Employee Performance at a Shoe Factory in Bandung - Adinda Nuraini; Ester Manik (Journal of Economics, Management, and Entrepreneurship, 2025)
This study aims to determine the effect enjoyment of work and job crafting on employee performance at a shoe factory in Bandung. This research is based on fluctuations in employee performance over the past few years and pre-survey results indicating suboptimal employee performance. The method used was descriptive and verification analysis with 86 respondents from 593 employees. The analysis was conducted using correlation, path analysis, and coefficient of determination. The results of the study indicate that enjoyment of work, job crafting, and employee performance yielded quite good results. There is a positive relationship between enjoyment of work and job crafting with a correlation of 0.887 and a coefficient of determination of 80.1%. The direct effect of enjoyment of work on employee performance is 13.1%, while the direct effect of job crafting is 31.1%. The indirect effect of both enjoyment of work and job crafting is 17.9%. The total effect of enjoyment of work and job crafting is 80.1%, while 19.9% is influenced by other variables not studied. The results emphasize the necessity for managers to adopt output-based management practices rather than rigid time-based systems. This shift can foster a culture of responsibility and autonomy, motivating employees to take ownership of their work and enhancing their commitment to organizational objectives. Overall, the implications of this study can guide organizations in implementing effective strategies to improve employee engagement, satisfaction, and performance.